DINAMIKA PERUBAHAN PENGGUNAAN LAHAN INDUSTRI KAITANNYA DENGAN PDRB SEKTOR INDUSTRI DI JABODETABEK - Dewi Setyowati; Khursatul Munibah; Setia Hadi (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2015)
The development of industrial areas in Jabodetabek developed rapidly since the beginning of 1970. The rapid urban development in the Greater Jakarta resulted in the emergence of new areas on the outskirts of the city as a container for the growth of activities, such as industrial areas. This condition occurs because of the limited supply of urban land on a large scale, especially for industrial activities. The purpose of this study was to analyze changes in land use to non-industrial land to industrial land and its relation to the GDP in Jabodetabek industry and analyzes the factors that affect the industrial sector GDP. The method used in this research are the survey, GIS analysis and regression. The results showed that changes in land use (conversion) non industry to 1998 to the Year 2012 are in Bekasi largest by land use type housing, open space, and rice fields. Changes in land use non industry to positively correlate with changes in the industrial sector GDP in Jabodetabek.. Variables are a strong influence on the formation of GDP industrial sector, is a variable raw material. The development of industrial sites in Greater Jakarta tends to follow them main road network forease of accessibility. Keywords: Distribution of industrial land, Jabodetabek, industry